Nickel-based active material precursor, method for preparing same, nickel-based active material, and lithium secondary battery

By adopting a multi-center structure nickel-based active material precursor, the problems of large transfer distance of lithium ions, low charge and discharge efficiency and short battery life in lithium secondary batteries are solved, and higher lithium ion utilization efficiency and battery capacity characteristics are achieved.

CN119503912APending Publication Date: 2025-02-25SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411526770.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-06-26
Filing Date
2019-06-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the charging and discharging process of the positive electrode active materials of existing lithium secondary batteries, the migration distance of lithium ions is large, resulting in low charging/discharging efficiency and cracks occur during long-term use, resulting in short battery life and poor capacity characteristics.

Method used

A nickel-based active material precursor is employed, which consists of a plurality of granular structures, each of which comprises a porous core portion and a shell portion, which consists of radially arranged primary particles and secondary particles having multiple radial centers. The growth and structure of particles are controlled by specific preparation methods, including multi-step feed rate and stirring operations.

Benefits of technology

It improves the availability of lithium ions, shortens the migration distance of lithium ions, enhances charging/discharge efficiency, reduces cracks caused by volume changes in the active material during charging and discharging, extends the battery life and improves capacity characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503912A_ABST
    Figure CN119503912A_ABST
Patent Text Reader

Abstract

The present invention relates to a nickel-based active material precursor, a method for preparing the same, a nickel-based active material, and a lithium secondary battery. A nickel-based active material precursor for a lithium secondary battery includes a secondary particle including a plurality of particulate structures, in which each particulate structure includes a porous core portion and a shell portion, the shell portion includes primary particles radially arranged on the porous core portion, and the secondary particle has a plurality of radial centers. When the nickel-based active material precursor for a lithium secondary battery is used, a nickel-based active material in which intercalation and deintercalation of lithium are promoted and the diffusion distance of lithium ions is short can be obtained. A lithium secondary battery manufactured using the nickel-based active material exhibits improved lithium availability and exhibits improved capacity and lifespan due to suppressed occurrence of cracks in the active material according to charging and discharging.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention application (invention name: Nickel-based active material precursor, preparation method thereof, nickel-based active material and lithium secondary battery, application date: June 26, 2019; application number: 201910571521.5).

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of Korean Patent Application No. 10-2018-0073588 filed on June 26, 2018, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0004] One or more embodiments relate to a nickel-based active material precursor for a lithium secondary battery, a method for preparing the nickel-based active material precursor, a nickel-based active material for a lithium secondary battery formed from the nickel-based active material precursor, and a lithium secondary battery including a positive electrode containing the nickel-based active material. Background Art

[0005] With the development of portable electronic devices, communication equipment, etc., there is an urgent need to develop lithium secondary batteries with high energy density. However, such lithium secondary batteries with high energy density may present reduced safety, so there is a need for improvement in this regard. As positive electrode active materials for such lithium secondary batteries, lithium nickel manganese cobalt composite oxides, lithium cobalt oxides, etc. are used. However, when these positive electrode active materials are used, the migration distance of lithium ions is determined according to the size of secondary particles during charging and discharging, and due to such physical distance, the charging / discharging efficiency is not high. In addition, with the repetition of the charging and discharging process, cracks appear in the primary particles, so the lithium secondary battery presents a degraded long-term life, increased resistance and unsatisfactory capacity characteristics, and therefore, there is still a need for improvement. Summary of the invention

[0006] One or more embodiments include a nickel-based active material precursor for a lithium secondary battery that exhibits improved lithium ion availability.

[0007] One or more embodiments include a method of preparing the above-described nickel-based active material precursor.

[0008] One or more embodiments include a nickel-based active material obtained from the above nickel-based active material precursor and a lithium secondary battery including a positive electrode including the nickel-based active material.

[0009] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.

[0010] According to one or more embodiments, a nickel-based active material precursor for a lithium secondary battery includes secondary particles comprising a plurality of granular structures, wherein each granular structure includes a porous core portion and a shell portion, the shell portion includes primary particles radially (radially) arranged on the porous core portion, and the secondary particles have a plurality of radial centers.

[0011] According to one or more embodiments, a method for preparing a nickel-based active material precursor for a lithium secondary battery includes: a first operation of supplying a raw material at a first feeding rate and stirring the raw material to form a precursor seed; a second operation of supplying a raw material at a second feeding rate to the precursor seed formed by the first operation and stirring the resulting mixture to grow the precursor seed by agglomeration of the mixture; and a third operation of supplying a raw material at a third feeding rate to precursor particles grown by the second operation and stirring the resulting mixture to control the growth of the precursor particles, wherein the supply raw material includes a complexing agent, a pH adjuster, and a metal raw material for forming a nickel-based active material precursor, and for the metal raw material for forming a nickel-based active material precursor, the second feeding rate is higher than the first feeding rate, and the third feeding rate is higher than the second feeding rate.

[0012] According to one or more embodiments, provided is a nickel-based active material for a lithium secondary battery, the nickel-based active material being obtained from the nickel-based active material precursor.

[0013] According to one or more embodiments, a lithium secondary battery includes a positive electrode including the nickel-based active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:

[0015] Figure 1 is a schematic diagram of secondary particles included in a nickel-based active material precursor according to an embodiment;

[0016] Figure 2A To include in Figure 1 A schematic partial perspective view of a granular structure in a secondary particle;

[0017] Figure 2B To include in Figure 1 A more detailed partial perspective view of the granular structure in the secondary particle;

[0018] Figure 3A schematic diagram for explaining a comparison of migration distances of lithium ions between a nickel-based active material B according to an embodiment and a general nickel-based active material A; and

[0019] Figure 4 is a diagram of a lithium secondary battery according to example embodiments.

[0020] Figure 5 A cross-sectional scanning electron microscopy (SEM) image of a secondary particle having a multi-center structure including 3 or 4 radial centers of the nickel-based active material precursor of Preparation Example 1.

[0021] Figure 6 A cross-sectional scanning electron microscopy (SEM) image of a secondary particle having a multi-center structure including 3 or 4 radial centers of the nickel-based active material precursor of Preparation Example 2. DETAILED DESCRIPTION

[0022] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals represent the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects of the present description. As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items.

[0023] Hereinafter, a nickel-based active material precursor for a lithium secondary battery according to an embodiment of the present disclosure, a method for preparing the nickel-based active material precursor, a nickel-based active material formed therefrom, and a lithium secondary battery including a positive electrode containing the nickel-based active material will be described in detail. The following is provided for illustrative purposes only and is not intended to limit the scope of the present disclosure, and the present disclosure should be limited only by the scope of the appended claims.

[0024] As used herein, the term "granular structure" refers to a structure in the form of particles formed by agglomeration of a plurality of primary particles.

[0025] As used herein, the term “isotropic arrangement” refers to an arrangement in which properties of an object do not change even when the direction in which the object is observed changes, and refers to an arrangement whose orientation (direction) is unknown (unestablished).

[0026] As used herein, the term "multi-center" refers to multiple centers in a single particle. In the case of multi-center particles, the length of lithium ion migration from the surface of the particle to the center is shortened. Due to the shortened migration distance of lithium ions, a particle structure with reduced internal resistance and more suitable for providing high charge / discharge efficiency and long life is obtained. As used herein, the term "multiple centers" refers to 2 or more centers, 3 or more centers, 4 or more centers, 5 or more centers, or 10 or more centers.

[0027] As used herein, the term "radial center" refers to the center of a granular structure comprising a porous core portion and a shell portion, the shell portion comprising primary particles radially arranged on the porous core portion, such as Figure 2A and 2B as shown in .

[0028] As used herein, the term "radial" refers to a form in which the major axis of the primary particles included in the shell portion is arranged perpendicular to the surface of the granular structure or forms an angle of ±30 degrees with respect to the vertical direction, such as Figure 2A and 2B as shown in .

[0029] As used herein, the term "size" of a particle refers to the average diameter when the particle is spherical and the average major axis length when the particle is non-spherical. The average diameter is the median particle diameter (D50), which is defined as the particle diameter corresponding to the cumulative diameter distribution at 50%, which means that 50% of the samples are below the particle diameter. The size of a particle can be measured using a particle size analyzer (PSA).

[0030] As used herein, the term "pore size" refers to the average diameter of the pores or the width of the opening of the pores when the pores are spherical or circular. When the pores are non-spherical or non-circular, such as elliptical, the pore size refers to the average major axis length.

[0031] As used herein, the term "irregular porous pores" refers to pores having irregular pore sizes and shapes and not having uniformity. Unlike the shell portion, the core portion including irregular porous pores may include amorphous particles, and unlike the shell portion, such amorphous particles are irregularly arranged.

[0032] In the following figures, the same reference numerals represent the same elements, and the size of each element in the figure is exaggerated for clarity and ease of description. In addition, the embodiments described herein are provided for illustrative purposes only, and various changes may be made to these embodiments. In addition, in the layer structure to be described below, the expression "above" or "on" includes not only "directly on", but also "on" without contact between two elements.

[0033] According to one embodiment, a nickel-based active material precursor for a lithium secondary battery includes secondary particles comprising a plurality of granular structures, wherein each granular structure includes a porous core portion and a shell portion, wherein the shell portion includes primary particles radially arranged on the porous core portion, and wherein the secondary particles have a plurality of radial centers.

[0034] Reference Figure 1 , a nickel-based active material precursor for a lithium secondary battery includes a secondary particle 200 including a plurality of granular structures 100. Referring to Figure 2A and 2B The granular structures 100 each include a porous core portion 10 and a shell portion 20, the shell portion 20 including primary particles 30 radially arranged on the porous core portion 10. Figure 1 , 2A 2B, the secondary particle 200 includes the granular structure 100, and each of the granular structure 100 has a radial center. Therefore, the secondary particle 200 has a plurality of radial centers.

[0035] Reference Figure 1 , 2A 2B, since the secondary particles 200 as the aggregate of the granular structure 100 have multiple radial centers, the diffusion distance of lithium ions during charge and discharge is shortened compared to the usual secondary particles composed of a single (single) granular structure. Therefore, in the nickel-based active material obtained from the nickel-based active material precursor composed of the secondary particles 200, the use of lithium ions is further promoted. In addition, since the granular structure 100 includes a porous core portion 10, and the primary particles 30 are radially arranged on the porous core portion 10 to form a shell portion 20, the volume change of the primary particles 30 during charge and discharge is effectively accommodated. Therefore, the appearance of cracks in the secondary particles 200 due to their volume change during charge and discharge is suppressed.

[0036] Reference Figure 2A and 2B, the shell portion 20 refers to a region of the granular structure 100 corresponding to about 30% to about 50% in length, for example, about 40% in length, from the outermost portion relative to the total distance between the center of the granular structure 100 and the surface, or a region within 2 µm from the surface of the granular structure 100. The porous core portion 10 refers to a region of the granular structure 100 corresponding to about 50% to about 70% in length, for example, 60% in length, from the center, relative to the total distance between the center of the granular structure 100 and the outermost portion, or the remaining region of the granular structure 100 except for the region within 2 µm from the surface. The center of the granular structure 100 is, for example, the geometric center of the granular structure 100. Although Figure 2A and 2B The granular structure 100 is shown to be completely spherical, but the granular structure 100 is spherical or non-spherical, without being limited thereto. The granular structure 100 may have a non-spherical shape, for example, one of a plurality of forms such as an elliptical, cubic, and rectangular parallelepiped forms, but the present disclosure is not limited thereto. Figure 2A and 2B The granular structure 100 has a completely granular form, but is obtained by assembling a plurality of granular structures 100. Figure 1 In the secondary particle 200, the granular structures 100 overlap each other and thus have a partial particle shape.

[0037] Reference Figure 1 , 2A and 2B, the secondary particle 200 has multiple centers and is composed of a plurality of granular structures 100 arranged isotropically. Since the secondary particle 200 includes the granular structure 100 and each granular structure 100 includes a porous core portion 10 corresponding to the center of the granular structure 100, the secondary particle 200 has multiple centers. Therefore, in the nickel-based active material obtained from the nickel-based active material precursor, the path through which lithium ions migrate from each center of the secondary particle 200 to the surface of the secondary particle 200 is shortened. Therefore, lithium ions are more easily utilized in the nickel-based active material obtained from the nickel-based active material precursor. In addition, in the nickel-based active material obtained from the nickel-based active material precursor, since the granular structure 100 included in the secondary particle 200 has an isotropic arrangement without a certain orientation, uniform utilization of lithium ions is possible regardless of the specific direction in which the secondary particles 200 are arranged. Refer to Figure 3In the nickel-based active material obtained from the nickel-based active material precursor, in the case of the secondary particle A composed of a single granular structure, the first migration distance L1 of the lithium ions corresponds to the radius of the secondary particle A, but in the case of the secondary particle B composed of a plurality of granular structures, the second migration distance L2 of the lithium ions corresponds to the radius of each granular structure, and thus the second migration distance L2 is smaller than the first migration distance L1. Therefore, in the nickel-based active material obtained from the nickel-based active material precursor, lithium ions are more easily utilized without increasing the nickel content, resulting in an increased discharge capacity.

[0038] Reference Figure 1 , 2A 2B, the major axis 31 of the primary particle constituting the surface of the secondary particle 200 may point to the normal of the surface of the secondary particle 200. For example, the (100) plane or the (110) plane is set in the direction of the major axis 31 of the primary particle constituting the surface of the secondary particle 200. In 50% or more, about 50% to about 90%, about 60% to about 90%, or about 70% to about 80% of the primary particles constituting the surface of the secondary particle 200, the major axis 31 of the primary particle may point to the normal of the surface of the secondary particle. For example, in 50% or more, about 50% to about 90%, about 60% to about 90%, or about 70% to about 80% of the primary particles constituting the surface of the secondary particle 200, the major axis 31 of the primary particle constituting the surface of the secondary particle 200 may be set in the direction of the normal of the (100) plane or the (110) plane of the primary particle at the outer surface of the secondary particle. When the major axis 31 of the primary particle constituting the surface of the secondary particle 200 points to the normal line of the surface of the secondary particle 200, for example, when the major axis 31 of the primary particle at the surface of the secondary particle 200 is arranged in the normal direction of the (100) plane or the (110) plane of the primary particle constituting the surface of the secondary particle 200 or when the direction of the major axis 31 of the primary particle constituting the surface of the secondary particle 200 is the

[100] direction or the

[110] direction, the diffusion of lithium at the interface between the nickel-based active material and the electrolyte solution is promoted, and the diffusion of lithium ions into the nickel-based active material is also promoted. Therefore, in the nickel-based active material obtained from the nickel-based active material precursor composed of the secondary particle 200, the utilization of lithium ions is further promoted.

[0039] Reference Figure 1The secondary particles 200 are, for example, spherical or non-spherical, depending on the aggregate form of the granular structure 100. The most common particles of the secondary particles 200 have a sphericity of about 0.850 to about 0.980, or about 0.880 to about 0.950. Since the nickel-based active material precursor has such a sphericity and the nickel-based active material obtained therefrom has a sphericity within the above range, the utilization of lithium ions is further promoted.

[0040] Reference Figure 2B In an example embodiment, the primary particle 30 is a non-spherical particle having a short axis and a long axis. The short axis is the axis connecting the points with the smallest distance at the opposite ends of the primary particle 30, and the long axis is the axis connecting the points with the largest distance at the opposite ends of the primary particle 30. The ratio of the short axis to the long axis of the primary particle 30 is in the range of, for example, about 1:2 to about 1:20, about 1:3 to about 1:20, or about 1:5 to about 1:15. Since the primary particle 30 has a ratio of the short axis to the long axis in the above range, the utilization of lithium ions in the nickel-based active material obtained from the nickel-based active material precursor is further promoted.

[0041] Reference Figure 2B, the primary particles 30 as non-spherical particles include, for example, plate-like particles. Plate-like particles are particles having two opposite surfaces separated from each other, and having a surface length greater than the thickness (which is the distance between the two surfaces). The length of the surface of a plate-like particle is the larger of the two lengths defining the surface of the plate-like particle. The two lengths defining the surface are different or the same from each other and are greater than the thickness of the plate-like particle. The thickness of the plate-like particle is the length of the short axis of the plate-like particle, and the length of the surface of the plate-like particle is the length of the long axis of the plate-like particle. The surface of the plate-like particle may be, but is not limited to, in the form of a polyhedron such as a trihedron, a tetrahedron, a pentahedron, a hexahedron, etc., a circular shape, or an elliptical shape, and any form of the surface of the plate-like particle that can be used in the art is possible. Examples of the plate-like particles include nanodisks, quadrilateral nanosheets, pentagonal nanosheets, and hexagonal nanosheets. The specific form of the plate-like particles varies depending on the specific conditions for preparing the secondary particles. The two opposite surfaces of the plate-like particles may not be parallel to each other, the angle between the surface and the side surface may be changed differently, the edges of the surface and the side surface may have a rounded shape, and the surface and the side surface may each have a plane or a curved shape. The long axis of the plate-like particles is radially arranged on the porous core portion 10 of the granular structure 100, thereby forming a shell portion 20. The length ratio of the minor axis to the major axis of the plate-like particles is, for example, in the range of about 1:2 to about 1:20, about 1:3 to about 1:20, or about 1:5 to about 1:15. In an example embodiment, the plate-like particles have an average thickness of about 100 nm to about 250 nm, or about 100 nm to about 200 nm and have an average surface length of about 250 nm to about 1,100 nm, or about 300 nm to about 1,000 nm. The average surface length of the plate-like particles is about 2 times to about 10 times the average thickness. Since the plate-like particles have a thickness, an average surface length and a ratio thereof within the above ranges, the radial arrangement of the plate-like particles on the porous core portion is further promoted, and therefore, the utilization of lithium ions in the nickel-based active material obtained from the nickel-based active material precursor is further promoted.

[0042] Reference Figure 1 In the nickel-based active material precursor, the secondary particles 200 have a size of, for example, about 5 µm to about 25 µm, or about 8 µm to about 20 µm. Since the secondary particles 200 have a size within the above range, the utilization of lithium ions in the nickel-based active material is further promoted. Figure 1 , 2Aand 2B, in the nickel-based active material precursor, the granular structure 100 has a size of, for example, about 2 µm to about 7 µm, about 3 µm to about 6 µm, about 3 µm to about 5 µm, or about 3 µm to about 4 µm. Since the granular structure 100 has a size within the above range, it is easier to form an isotropic arrangement by the collection of a plurality of granular structures 100, and the utilization of lithium ions in the nickel-based active material obtained from the nickel-based active material precursor is further promoted.

[0043] Reference Figure 2A and 2B , the pore size in the porous core part 10 included in the granular structure 100 is in the range of about 150 nm to about 1 μm, about 150 nm to about 550 nm, or about 200 nm to about 800 nm. In addition, the pore size in the shell part 20 included in the granular structure 100 is less than 150 nm, 100 nm or less, or in the range of about 20 nm to about 90 nm. The porous core part 10 included in the granular structure 100 has a porosity of about 5% to about 15%, or about 5% to about 10%. In addition, the shell part 20 included in the granular structure 100 has a porosity of about 1% to about 5%, or about 1% to about 3%. Since the granular structure 100 has a pore size and porosity within the above range, the nickel-based active material obtained by the nickel-based active material precursor has excellent capacity characteristics. In an example embodiment, in the granular structure 100, the porosity of the shell portion 20 is controlled to be less than the porosity of the porous core portion 10. For example, the pore size and porosity of the porous core portion 10 are greater than those of the shell portion 20, and are irregularly controlled. When the porosity of the porous core portion 10 and the shell portion 20 of the granular structure 100 satisfies the above range and relationship, the density of the shell portion 20 is increased compared to the porous core portion 10, and thus the side reaction between the granular structure 100 and the electrolyte solution is effectively suppressed. The pore size and porosity can be measured by a gas adsorption method.

[0044] According to example embodiments, in the granular structure 100, closed pores may exist in the porous core portion 10, and closed pores and / or open pores may exist in the shell portion 20. Although it is difficult to include an electrolyte, etc. for the closed pores, the open pores enable the electrolyte, etc. to be included in the pores of the granular structure 100. In addition, irregular porous pores may exist in the porous core portion 10 of the granular structure 100. Like the shell portion 20, the porous core portion 10 including an irregular porous structure includes plate-like particles, and unlike the shell portion 20, the plate-like particles of the porous core portion 10 are irregularly arranged.

[0045] The nickel-based active material precursor may be a compound represented by the following Formula 1:

[0046] [Formula 1]

[0047] Ni 1-x-y-z Co x Mn y M z (OH)2

[0048] Wherein, in Formula 1, M is an element selected from the following: boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zirconium (Zr), tungsten (W), and aluminum (Al), x ≤ (1 - x - y - z), y ≤ (1 - x - y - z), 0 < x < 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < 1 - x - y - z < 1. Therefore, in the nickel-based active material precursor of Formula 1, the content of nickel is equal to or greater than the content of cobalt, and the content of nickel is equal to or greater than the content of manganese. In Formula 1, 0 < x ≤ 1 / 3, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.05, and 1 / 3 ≤ (1 - x - y - z) ≤ 0.95. According to one embodiment, in Formula 1, x may be 0.1 to 0.3, y may be 0.05 to 0.3, and z may be 0.

[0049] The nickel-based active material precursor may be, for example, Ni 0.6 Co 0.2 Mn 0.2 (OH)2, Ni 0.7 Co 0.15 Mn 0.15 (OH)2, Ni 0.7 Co 0.1 Mn 0.2 (OH)2, Ni 0.5 Co 0.2 Mn 0.3 (OH)2, Ni 1 / 3 Co 1 / 3 Mn 1 / 3 (OH)2, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, or Ni 0.85 Co 0.1 Al 0.05 (OH)2.

[0050] According to another embodiment, a method for preparing a nickel-based active material precursor includes: a first operation of supplying a raw material at a first feed rate and stirring the raw material to form a precursor seed; a second operation of supplying a raw material at a second feed rate to the precursor seed formed by the first operation and stirring the raw material to grow the precursor seed; and a third operation of supplying a raw material at a third feed rate to the precursor seed grown by the second operation and stirring the raw material to control the growth of the precursor seed, wherein the supply raw material includes a complexing agent, a pH adjuster, and a metal raw material for forming a nickel-based active material precursor, and for the metal raw material for forming a nickel-based active material precursor, the second feed rate is higher than the first feed rate, and the third feed rate is higher than the second feed rate.

[0051] In the first operation, the second operation and the third operation, as the feed rate of the metal raw material is sequentially increased, a nickel-based active material precursor having the novel structure is obtained. In the first operation, the second operation and the third operation, respectively, the reaction temperature is in the range of about 40 ° C. to about 60 ° C., the stirring power is about 0.5 kW / m 3 About 6.0 kW / m 3 In the range of about 10 to about 12, the pH is in the range of about 10 to about 12, and the amount of the complexing agent included in the reaction mixture is in the range of about 0.3 M to about 0.6 M, for example, in the range of about 0.35 M to about 0.45 M. Within the above range, a nickel-based active material precursor that more satisfactorily matches the above structure can be obtained. The stirring power is proportional to the stirring rate.

[0052] In the first operation, the pH is controlled while: the metal raw material and the complexing agent are added at a constant rate to a reactor including an aqueous solution containing a complexing agent and / or a pH adjusting agent whose pH is controlled, thereby forming and growing precursor seeds. In the first operation, the precursor particles have a growth rate of about 0.30 ± 0.05 μm / hour. In the first operation, the stirring power of the reaction mixture can be about 1.5 kW / m 3 About 4 kW / m 3 Within the range of 3.0 kW / m 3, and the pH may be in the range of about 10.0 to about 12.0. For example, in the first operation, the feed rate of the metal raw material is in the range of greater than about 0 L / hour to about 10.0 L / hour, such as 5.0 L / hour, and the feed rate of the complexing agent is about 0.1 times to about 0.6 times, such as 0.12 times, the molar feed rate of the metal raw material. The temperature of the reaction mixture is in the range of about 40 ° C to about 60 ° C, such as 50 ° C, and the pH of the reaction mixture is in the range of about 10.5 to about 11.50.

[0053] In the second operation, the reaction conditions are changed to grow the precursor seeds formed by the first operation. The growth rate of the precursor seeds in the second operation is the same as the growth rate of the precursor seeds in the first operation or is increased by 20% or more than the growth rate of the precursor seeds in the first operation. The feed rate of the metal raw material in the second operation is 1.2 times or more, for example, about 1.2 times to about 2.5 times, of the feed rate of the metal raw material in the first operation, and the concentration of the complexing agent in the reaction mixture may be increased by 0.05 M or more, for example, about 0.05 M to about 0.15 M relative to the concentration of the complexing agent in the first operation. In the second operation, the stirring power of the reaction mixture may be about 1 kW / m 3 About 3 kW / m 3 In the range of 2.5 kW / m 3 , and the pH of the reaction mixture may be in the range of about 10.5 to about 11.0. The precursor particles obtained in the second operation may have an average particle size (D50) of about 9 μm to about 12 μm, for example, about 10 μm.

[0054] In the third operation, the growth rate of the precursor seed particles is adjusted to obtain a nickel-based active material precursor for a lithium secondary battery. When the average particle size (D50) of the precursor particles in the second operation reaches about 9 μm to about 12 μm, for example, about 10 μm, the third operation is performed. The growth rate of the precursor particles in the third operation may be increased by 2 times or more, for example, 3 times or more than the growth rate of the precursor particles in the second operation. To this end, the reaction product in the reactor that has undergone the second operation may be partially removed to dilute the concentration of the reaction product in the reactor. The product removed from the inside of the reactor may be used in other reactors. The feed rate of the metal raw material in the third operation may be 1.1 times or more, for example, about 1.1 times to about 1.5 times, of the feed rate of the metal raw material in the second operation, and the concentration of the complexing agent in the reaction mixture may be the same as the concentration of the complexing agent in the second operation, or may be increased by 0.05 M or more, for example, about 0.05 M to about 0.15 M relative to the concentration of the complexing agent in the second operation. In the third operation, the precipitate is rapidly grown to thereby obtain a nickel-based active material precursor. In the third operation, the stirring power of the reaction mixture is about 0.5 kW / m 3 About 2kW / m 3 In the range of 1 kW / m 3 , and the reaction mixture may have a pH of about 10.5 to about 11.

[0055] In the precursor preparation method, as the first operation, the second operation, and the third operation proceed, the feed rate of the metal raw material may be sequentially increased. For example, the feed rate of the metal raw material in the second operation may be increased by about 10% to about 50% relative to the feed rate of the metal raw material in the first operation, and the feed rate of the metal raw material in the third operation may be increased by about 10% to about 50% relative to the feed rate in the second operation. Therefore, by gradually increasing the feed rate of the metal raw material, a nickel-based active material precursor that more satisfactorily matches the above structure may be obtained.

[0056] In the precursor preparation method, as the metal raw material, the composition of the nickel-based active material precursor can be considered, and the metal precursor corresponding thereto can be used. Examples of the metal raw materials include, but are not limited to, metal carbonates, metal sulfates, metal nitrates, metal chlorides and metal fluorides, and any metal precursor that can be used in the art is possible. For example, as a nickel (Ni)-containing compound, at least one selected from nickel sulfate, nickel nitrate, nickel chloride and nickel fluoride can be used. For example, as a metal (M)-containing compound, at least one selected from manganese sulfate, manganese nitrate, manganese chloride, manganese fluoride, cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt fluoride can be used.

[0057] In the precursor preparation method, as the first operation, the second operation, and the third operation proceed, the stirring power of the reaction mixture in the reactor may be sequentially reduced. In the first operation, the stirring power may be about 1.5 kW / m 3 About 4 kW / m 3 In the range of about 1 kW / m 3 About 3 kW / m 3 In the third operation, the stirring power may be about 0.5 kW / m 3 About 2 kW / m 3 In this way, by gradually reducing the stirring power, a nickel-based active material precursor that more satisfactorily matches the above structure can be obtained. In addition, in the precursor preparation method, as the first operation, the second operation, and the third operation proceed, the stirring rate of the reaction mixture in the reactor can be sequentially reduced. In this way, by gradually reducing the stirring rate, a nickel-based active material precursor that more satisfactorily matches the above structure can be obtained.

[0058] In the precursor preparation method, as the first operation, the second operation and the third operation proceed, the pH of the reaction mixture in the reactor may be maintained or sequentially reduced. For example, the pH of the reaction mixture in the first to third operations may be in the range of about 10.0 to about 11.50 at a reaction temperature of 50 ° C. For example, when the reaction temperature is 50 ° C, the pH of the reaction mixture in the third operation may be the same as the pH of the reaction mixture in the first operation, or may be about 0.5 to about 1.5 or about 0.5 to about 1.0 lower than the pH of the reaction mixture in the first operation. For example, at a reaction temperature of 50 ° C, the pH of the reaction mixture in the second operation may be the same as the pH of the reaction mixture in the first operation, or may be about 0.5 to about 1.0 lower than the pH of the reaction mixture in the first operation, and the pH of the reaction mixture in the third operation may be the same as the pH of the reaction mixture in the second operation, or may be about 0.35 to about 0.55 lower than the pH of the reaction mixture in the second operation. In this way, by maintaining or gradually reducing the pH of the reaction mixture, a nickel-based active material precursor that more satisfactorily matches the above structure can be obtained.

[0059] In the precursor preparation method, the concentration of the complexing agent included in the reaction mixture of the second operation may be maintained or increased relative to the concentration of the complexing agent included in the reaction mixture of the first operation, and the concentration of the complexing agent included in the reaction mixture of the third operation may be maintained or increased relative to the concentration of the complexing agent included in the reaction mixture of the second operation.

[0060] In order to control the growth rate of the nickel-based active material precursor particles, the amount of the metal raw material added for particle growth in the second operation may be increased by about 15% to about 35%, for example, about 25%, compared to the first operation, and the amount of the metal raw material added for particle growth in the third operation may be increased by about 20% to about 35%, for example, about 33%, compared to the second operation. In addition, the feeding rate of the complexing agent (e.g., aqueous ammonia) in the second operation may be increased by 10% to about 30%, for example, about 20%, relative to the feeding rate of the complexing agent (e.g., aqueous ammonia) in the first operation, thereby increasing the density of the particles.

[0061] The pH regulator is used to reduce the solubility of metal ions in the reactor so that the metal ions are precipitated into hydroxides. The pH regulator is, for example, sodium hydroxide (NaOH), sodium carbonate (Na2CO3), etc. The pH regulator is, for example, NaOH.

[0062] The complexing agent controls the formation reaction rate of the precipitate in the coprecipitation reaction. The complexing agent may be ammonium hydroxide (NH4OH) (ammonia water), citric acid, acrylic acid, tartaric acid, glycolic acid, etc. The amount of the complexing agent is used at a normal level. The complexing agent is, for example, ammonia water.

[0063] The nickel-based active material according to another embodiment is obtained from the above nickel-based active material precursor. The nickel-based active material is, for example, a compound represented by the following formula 2:

[0064] [Formula 2]

[0065] Li a (Ni 1-x-y-z Co x Mn y M z )O2

[0066] Wherein, in formula 2, M is an element selected from: B, Mg, Ca, Sr, Ba, Ti, W, V, Cr, Fe, Cu, Zr, and Al, 1.0 ≤ a ≤ 1.3, x ≤ (1 - x - y - z), y ≤ (1 - x - y - z), 0 < x < 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < 1 - x - y - z < 1.

[0067] In the compound of formula 2, the content of nickel is greater than the content of cobalt and greater than the content of manganese. In formula 2, 1.0 ≤ a ≤ 1.3, 0 < x ≤ 1 / 3, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.05, and 1 / 3 ≤ (1 - x - y - z) ≤ 0.95.

[0068] In formula 2, a may be, for example, 1 to 1.1, x may be 0.1 to 0.3, y may be 0.05 to 0.3, and z may be 0.

[0069] In the nickel-based active material, for example, the content of nickel may be in the range of about 33 mol% to about 95 mol%, such as about 50 mol% to about 90 mol%, such as about 60 mol% to about 85 mol%, relative to the total amount of transition metals. The total amount of transition metals refers to the total amount of nickel, cobalt, manganese, and M in formula 2.

[0070] The nickel-based active material may be, for example, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.15 Mn 0.15 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn0.3 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2, or LiNi 0.85 Co 0.1 Al 0.05 O2.

[0071] The nickel-based active material may have a particle structure and characteristics substantially the same as or similar to those of the above-described nickel-based active material precursor, except that lithium is arranged in a crystal structure and hydroxide becomes an oxide.

[0072] The secondary particles included in the nickel-based active material have multiple centers and are composed of a plurality of granular structures arranged isotropically, and thus the migration distance of lithium ions and electrons from the surface of the secondary particles to the central portion is shortened, and thus, the insertion and extraction of lithium ions are promoted and the migration of electrons is promoted. In addition, since the granular structure included in the nickel-based active material includes a porous core portion and primary particles radially arranged on the porous core portion, the volume change of the nickel-based active material is effectively accommodated during charging and discharging, and thus the stress of the nickel-based active material can be reduced. Therefore, the nickel-based active material obtained from the above-mentioned nickel-based active material precursor exhibits a higher capacity relative to the same composition without increasing the nickel content.

[0073] The method of preparing the nickel-based active material from the nickel-based active material precursor is not particularly limited, and may be, for example, a dry method.

[0074] The nickel-based active material may be prepared, for example, by mixing a lithium precursor and a nickel-based active material precursor at a certain molar ratio and subjecting the resulting mixture to a primary heat treatment (low-temperature heat treatment) at a temperature of about 600° C. to about 800° C.

[0075] The lithium precursor is, for example, lithium hydroxide, lithium fluoride, lithium carbonate, or a mixture thereof. For example, the mixing ratio of the lithium precursor to the nickel-based active material precursor is stoichiometrically adjusted to prepare the nickel-based active material of Formula 2.

[0076] The mixing process may be dry mixing, and may be performed using a mixer or the like. A dry mixing process may be performed using a grinder. The grinding conditions are not particularly limited, but grinding may be performed so that the precursor used as the starting material undergoes little deformation, such as crushing, etc. The size of the lithium precursor mixed with the nickel-based active material precursor may be pre-controlled. The size (average particle size) of the lithium precursor is in the range of about 5 μm to about 15 μm, for example, about 10 μm. By grinding the lithium precursor and the precursor having such a size at about 300 rpm to about 3,000 rpm, a desired mixture may be obtained. During the grinding process, when the internal temperature of the mixer rises by 30 ° C or more, a cooling process may be performed so that the internal temperature of the mixture is maintained at room temperature (25 ° C).

[0077] Low temperature heat treatment is carried out in an oxidizing gas atmosphere. The oxidizing gas atmosphere uses an oxidizing gas such as oxygen or air, and the oxidizing gas is composed of, for example, about 10% by volume to about 20% by volume of oxygen or air and about 80% by volume to about 90% by volume of an inert gas. As the reaction between the lithium precursor and the nickel-based active material precursor proceeds, the low temperature heat treatment may be carried out at a densification temperature or lower. The densification temperature is a temperature at which sufficient crystallization is performed to achieve the charge capacity that the active material can provide. The low temperature heat treatment is carried out at a temperature of, for example, about 600°C to about 800°C, for example, about 650°C to about 800°C. The low temperature heat treatment time varies depending on the heat treatment temperature, but is, for example, in the range of about 3 hours to about 10 hours.

[0078] The method for preparing a nickel-based active material may further include: after the low-temperature heat treatment, a second heat treatment (high-temperature heat treatment) process is performed in an oxidizing gas atmosphere by suppressing exhaust from the inside of the reactor. The high-temperature heat treatment is performed at a temperature of, for example, about 700 ° C to about 900 ° C. The high-temperature heat treatment time varies depending on the high-temperature heat treatment temperature, but is, for example, in the range of about 3 hours to about 10 hours.

[0079] According to another embodiment, a lithium secondary battery includes a positive electrode including the above-described nickel-based active material for a lithium secondary battery, a negative electrode, and an electrolyte disposed therebetween.

[0080] The method of manufacturing the lithium secondary battery is not particularly limited, and any method used in the art may be used. The lithium secondary battery may be manufactured by, for example, the following method.

[0081] The positive electrode or the negative electrode is manufactured respectively by applying a composition for forming a positive electrode active material layer and a composition for forming a negative electrode active material layer to corresponding current collectors and drying the resulting structure.

[0082] The composition for forming a positive electrode active material layer is prepared by mixing a positive electrode active material, a conductive agent, a binder, and a solvent, and the positive electrode active material according to one embodiment is used as the positive electrode active material.

[0083] The binder is a component that helps the bonding between the active material and the conductive agent and the bonding between the active material and the current collector, and is added in an amount of about 0.1 parts by weight to about 50 parts by weight of the total amount of the positive electrode active material of 100 parts by weight. Non-limiting examples of the binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers.

[0084] The conductive agent may be added in an amount of about 0.5 parts by weight to about 50 parts by weight of the total amount of the positive electrode active material of 100 parts by weight. The conductive agent is not particularly limited as long as it does not cause any chemical changes in the manufactured battery and has conductivity, and non-limiting examples thereof include: graphite such as natural graphite or artificial graphite; carbonaceous materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorinated carbon powder; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives.

[0085] The amount of the solvent is about 10 parts by weight to about 300 parts by weight relative to 100 parts by weight of the total weight of the positive electrode active material. When the amount of the solvent is within the above range, the formation of the positive electrode active material layer can be further promoted. As a non-limiting example of the solvent, N-methylpyrrolidone and the like are used.

[0086] The amounts of the binder, the conductive agent, and the solvent are at normal levels.

[0087] The positive electrode current collector has a thickness of about 3 μm to about 500 μm, and is not particularly limited as long as it has high conductivity without causing chemical changes in the manufactured battery. Examples of the positive electrode current collector include stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector may be processed to have fine irregularities on its surface to enhance the bonding strength of the current collector to the positive electrode active material, and may include any of a variety of forms including films, sheets, foils, nets, porous structures, foams, and non-woven fabrics.

[0088] Separately, the composition for forming the negative electrode active material layer is prepared by mixing a negative electrode active material, a binder, a conductive agent and a solvent. As the negative electrode active material, a material capable of inserting and extracting lithium ions is used. As non-limiting examples of the negative electrode active material, graphite, a carbonaceous material such as carbon, Li metal or its alloy, or a silicon oxide-based material can be used.

[0089] The binder is added in an amount of about 0.5 parts by weight to about 50 parts by weight relative to 100 parts by weight of the total weight of the negative electrode active material. As a non-limiting example, the binder may be the same binder as that of the positive electrode.

[0090] The conductive agent is used in an amount of about 0 to about 5 parts by weight relative to 100 parts by weight of the total weight of the negative electrode active material. When the amount of the conductive agent is within the above range, the electrode finally obtained has excellent conductivity. For example, when graphite having good conductivity is used as the negative electrode active material, the conductive agent can be omitted in the negative electrode active material layer.

[0091] The amount of the solvent is in the range of about 10 parts by weight to about 300 parts by weight relative to 100 parts by weight of the total weight of the negative electrode active material. When the amount of the solvent is in the above range, the operation for forming the negative electrode active material layer is easy. As non-limiting examples of the solvent, water, N-methylpyrrolidone and / or the like are used.

[0092] As the conductive agent and the solvent, the same conductive agent and solvent as those used in manufacturing the positive electrode may be used.

[0093] The negative electrode current collector is generally manufactured to a thickness of about 3 μm to about 500 μm. The negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes in the manufactured battery, and non-limiting examples of the negative electrode current collector include copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel treated with carbon, nickel, titanium, or silver, and aluminum-cadmium alloys. In addition, as in the positive electrode current collector, the current collector may be processed to have fine irregularities on its surface to enhance the bonding strength of the current collector to the negative electrode active material, and may include any of a variety of forms including films, sheets, foils, nets, porous structures, foams, and non-woven fabrics.

[0094] The separator is disposed between the positive electrode and the negative electrode manufactured through the above process.

[0095] The separator has a pore size of 0.01 μm to about 10 μm and generally has a thickness of about 5 μm to about 300 μm. For example, the separator may be an olefin-based polymer such as polypropylene, polyethylene, etc.; a sheet or non-woven fabric made of glass fiber; etc. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte may also serve as a separator.

[0096] The lithium salt-containing nonaqueous electrolyte is composed of a nonaqueous electrolyte and a lithium salt. As the nonaqueous electrolyte, a nonaqueous electrolyte solvent, an organic solid electrolyte, or an inorganic solid electrolyte can be used.

[0097] As the nonaqueous electrolyte solvent, any aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, N,N-dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate may be used, but the present disclosure is not limited thereto.

[0098] Non-limiting examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfides, polyvinyl alcohol, and polyvinylidene fluoride. Non-limiting examples of the inorganic solid electrolyte include Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.

[0099] The lithium salt is a material that is easily soluble in the nonaqueous electrolyte, and non-limiting examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, (FSO2)2NLi, lithium chloroborate, lithium lower aliphatic carboxylate, lithium tetraphenylborate, and lithium imide.

[0100] Figure 4 Schematic cross-sectional view illustrating the structure of a lithium secondary battery 1 according to an embodiment.

[0101] Reference Figure 4, the lithium secondary battery 1 includes a positive electrode 3, a negative electrode 2 and a separator 4. The positive electrode 3, the negative electrode 2 and the separator 4 are wound or folded and then housed in a battery case 5. Subsequently, an organic electrolyte solution is injected into the battery case 5 and the battery case 5 is sealed by a cap assembly 6, thereby completing the manufacture of the lithium secondary battery 1. The battery case 5 may have a cylindrical shape, a rectangular shape or a thin film shape. For example, the lithium secondary battery 1 may be a large-sized thin film type battery. The lithium secondary battery 1 may be a lithium ion battery.

[0102] The separator can be arranged between the positive electrode and the negative electrode to thereby form a battery assembly. The battery assembly is stacked in a double-cell structure and impregnated with an organic electrolyte solution, and the resulting structure is contained in a bag and hermetically sealed, thereby completing the manufacture of a lithium-ion polymer battery. In addition, a plurality of battery assemblies are stacked to form a battery pack, and the battery pack can be used in any device requiring high capacity and high power output. For example, the battery pack can be used in a notebook computer, a smart phone, an electric vehicle, etc. In addition, the lithium secondary battery can be used in an electric vehicle (EV) due to its excellent storage stability at high temperatures, excellent life characteristics, and excellent rate performance. For example, the lithium secondary battery can be used in a hybrid vehicle such as a plug-in hybrid electric vehicle (PHEV).

[0103] Hereinafter, the present disclosure will be described in further detail with reference to the following examples and comparative examples. However, these examples are provided for illustrative purposes only and are not intended to limit the scope of the present disclosure.

[0104] Preparation Example 1: Preparation of nickel-based active material precursor (6:2:2): three-step method

[0105] The nickel-based active material precursor (Ni 0.6 Co 0.2 Mn 0.2 (OH)2). In the following preparation process, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O) and manganese sulfate (MnSO4·H2O) as metal raw materials for forming a nickel-based active material precursor are dissolved in distilled water as a solvent at a molar ratio of 6:2:2 to prepare a mixed solution. In addition, sodium hydroxide (NaOH) and ammonia water (NH4OH) as precipitants are prepared to form a complex compound.

[0106] Step 1: 5.0 L / hour feed rate, 1.5 kW / m 3 Stirring power, NH4OH 0.35M, 10.5 to 11.0 pH

[0107] Ammonia water was added to the reactor equipped with a stirrer at a concentration of 0.35 mol / L (M). 3At the same time of the stirring power of 50 ° C and the reaction temperature of 50 ° C, the metal raw material (a mixed solution of nickel sulfate, cobalt sulfate and manganese sulfate) of 2 mol / L (M) and the ammoniacal liquor of 0.35 mol / L (M) were added at a feed rate of 5.0 L / hour and 0.53 L / hour, respectively. Subsequently, sodium hydroxide (NaOH) was added thereto to maintain the pH of the reaction mixture. The pH of the reaction mixture in the reactor was maintained at 10.5 to 11.0. The reaction mixture was stirred in such a pH range for 6 hours to allow the first step reaction to occur.

[0108] Step 2: 6.5 L / hour feed rate, 1.0 kW / m 3 Stirring power, NH4OH 0.40 M, 10.5 to pH 11.0

[0109] After 6 hours of the first step, the stirring power in the reactor was reduced to 1.0 kW / m 3 , and while maintaining the reaction temperature at 50 ° C, the metal raw material and 0.40 mol / L (M) of ammonia water were added at a feed rate of 6.5 L / hour and 0.77 L / hour, respectively. The pH of the reaction mixture in the reactor was maintained at 10.5 to 11.0. The reaction mixture was stirred for 16 hours until the particles in the reactor reached an average particle size (D50) of about 11 μm to allow the second step reaction to occur.

[0110] Step 3: 8.50 L / hour feed rate, 0.5 kW / m 3 Stirring power, NH4OH 0.40M, pH 10.5 to 11.0

[0111] After the second step, when the average particle size (D50) of the particles in the reactor reached about 11 µm, the stirring power in the reactor was reduced to 0.5 kW / m 3 , and while the reaction temperature is maintained at about 50 ° C, metal raw materials and 0.40 mol / L (M) of ammonia are added at a feed rate of 8.50 L / hour and 1.03 L / hour, respectively, and NaOH is added to maintain the pH of the reaction mixture. The pH of the solution in the reactor is maintained at 10.5 to 11.0. The reaction mixture is stirred for 5 hours in such a pH range to allow the third step reaction to occur. Subsequently, the slurry solution in the reactor is filtered and washed with high-purity distilled water, then dried in a hot air oven for 24 hours, thus obtaining an active material precursor (Ni based on nickel). 0.6 Co 0.2 Mn 0.2 (OH)2).

[0112] Preparation Example 2: Preparation of nickel-based active material precursor (7:1.5:1.5)

[0113] A mixed solution was prepared in the same manner as in Preparation Example 1, except that nickel sulfate (NiSO4.6H2O), cobalt sulfate (CoSO4.7H2O) and manganese sulfate (MnSO4.H2O) were mixed as metal raw materials at a molar ratio of 7:1.5:1.5 instead of 6:2:2, and a nickel-based active material precursor (Ni 0.7 Co 0.15 Mn 0.15 (OH)2).

[0114] Step 1: 5.0 L / hour feed rate, 3.0 kW / m 3 Stirring power, NH4OH 0.35 M, 11.0 to pH 11.5

[0115] Ammonia water was added to the reactor equipped with a stirrer at a concentration of 0.35 mol / L (M). 3 At 50 ℃ of reaction temperatures, 2 mol / L (M) of metal raw material (a mixed solution of nickel sulfate, cobalt sulfate and manganese sulfate) and 0.35 mol / L (M) of ammonia were added at a feed rate of 5.0 L / hour and 0.53 L / hour, respectively. Subsequently, NaOH was added to maintain the pH of the reaction mixture. The pH of the reaction mixture in the reactor was maintained at 11.0 to 11.5. The reaction mixture was stirred within such a pH range for 6 hours to allow the first step reaction to occur.

[0116] Step 2: 6.50 L / hour feed rate, 2.5 kW / m 3 Stirring power, NH4OH 0.40 M, 10.5 to pH 11.00

[0117] After 6 hours of the first step, the stirring power in the reactor was reduced to 2.5 kW / m 3 , and while maintaining the reaction temperature at 50 ° C, the metal raw material and 0.40 mol / L (M) of ammonia water were added at a feed rate of 6.50 L / hour and 0.77 L / hour, respectively. The pH of the reaction mixture in the reactor was maintained at 10.5 to 11.0. The reaction mixture was stirred for 16 hours until the average particle size (D50) of the particles in the reactor reached about 10 μm to allow the second step reaction to occur.

[0118] Step 3: 8.50 L / hour feed rate, 2.0 kW / m 3 Stirring power, NH4OH 0.45 M, 10.5 to pH 11.0

[0119] After the second step reaction, when the average particle size (D50) of the particles in the reactor reached about 10 µm, the stirring power in the reactor was reduced to 2.0 kW / m 3, and while the reaction temperature is maintained at about 50 ° C, metal raw materials and 0.45 mol / L (M) of ammonia are added at a feed rate of 8.50 L / hour and 1.15 L / hour, respectively, and NaOH is added to maintain the pH of the reaction mixture. The pH of the reaction mixture in the reactor is maintained at 10.5 to 11.0. The reaction mixture is stirred for 6 hours in such a pH range to allow the third step reaction to occur. Subsequently, the slurry solution in the reactor is filtered and washed with high-purity distilled water, then dried in a hot air oven for 24 hours, thus obtaining an active material precursor (Ni based on nickel). 0.7 Co 0.15 Mn 0.15 (OH)2).

[0120] Comparative Preparation Example 1: Preparation of Nickel-Based Active Material Precursor (6:2:2): One-Step Method

[0121] In the following comparative preparation process, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O) and manganese sulfate (MnSO4·H2O) as metal raw materials for forming a nickel-based active material precursor are dissolved in distilled water as a solvent in a molar ratio of 6:2:2 to prepare a mixed solution, and in order to form a complex compound, NaOH and ammonia water (NH4OH) as precipitants are prepared.

[0122] Ammonia water was added to the reactor equipped with a stirrer at a concentration of 0.50 mol / L and the flow rate was maintained at 1.5 kW / m 3 At a stirring power of 100 and a reaction temperature of 50 ° C, 2 mol / L (M) of metal raw material and 0.50 mol / L (M) of ammonia water were added thereto at a feed rate of 6.00 L / hour and 1.4 L / hour, respectively, and NaOH was added to maintain the pH of the reaction mixture. The pH of the reaction mixture in the reactor was maintained at 11.4 to 11.6. The reaction mixture was stirred in such a pH range for 33 hours, and then when the reaction reached a normal state, the overflowed reaction product was collected.

[0123] The collected reaction product was washed and then dried by hot air at 150° C. for 24 hours, thereby preparing a nickel-based active material precursor (Ni 0.6 Co 0.2 Mn 0.2 (OH)2).

[0124] Comparative Preparation Example 2: Preparation of Nickel-based Active Material Precursor

[0125] A nickel-based active material precursor (Ni 0.6 Co 0.2 Mn 0.2(OH)2), except that the feed rate of the metal raw material in the second step was changed from 6.50 L / hour to 4.50 L / hour, and the concentration of aqueous ammonia in the reactor was changed from 0.40 mol / L to 0.30 mol / L. However, a large amount of fine powder was generated in the second step, so that the size of the particles could not be further increased.

[0126] Comparative Preparation Example 3: Preparation of Nickel-based Active Material Precursor

[0127] A nickel-based active material precursor (Ni 0.6 Co 0.2 Mn 0.2 (OH)2), except that the stirring power in the second step was reduced from 1.0 kW / m 3 Change to 3.0 kW / m 3 However, a large amount of fine powder was generated in the second step, so that the size of the particles could not be increased further.

[0128] Example 1: Preparation of nickel-based active materials

[0129] The composite metal hydroxide (Ni 0.6 Co 0.2 Mn 0.2 (OH)2) and lithium hydroxide (LiOH) were mixed in a molar ratio of 1:1 by a dry method and subjected to a heat treatment at about 700 ° C. in an oxygen atmosphere for 6 hours, thereby obtaining a nickel-based active material (LiNi 0.6 Co 0.2 Mn 0.2 The nickel-based active material was subjected to heat treatment at about 800° C. in an air atmosphere for 6 hours, thereby obtaining a nickel-based active material (LiNi 0.6 Co 0.2 Mn 0.2 O2): wherein the primary particle agglomerates are arranged in a multi-center isotropic manner through the dispersion of at least two of the radial centers of the primary particles.

[0130] Example 2: Preparation of nickel-based active materials

[0131] A nickel-based active material was prepared in the same manner as in Example 1, except that the nickel-based active material precursor prepared according to Preparation Example 2 was used instead of the nickel-based active material precursor of Preparation Example 1.

[0132] Comparative Example 1: Preparation of nickel-based active materials

[0133] A nickel-based active material was prepared in the same manner as in Example 1, except that the nickel-based active material precursor prepared according to Comparative Preparation Example 1 was used instead of the nickel-based active material precursor of Preparation Example 1.

[0134] Manufacturing Example 1: Manufacturing of coin cell battery

[0135] The nickel-based active material (LiNi 0.6 Co 0.2 Mn 0.2 O2) as the positive electrode active material to manufacture coin unit batteries.

[0136] 96 g of the nickel-based active material (LiNi 0.6 Co 0.2 Mn 0.2 O2), 2 g of polyvinylidene fluoride, 47 g of N-methylpyrrolidone as a solvent and 2 g of carbon black as a conductive agent were uniformly dispersed using a mixer after removing air bubbles therefrom, thereby preparing a slurry for forming a positive electrode active material layer.

[0137] The slurry prepared according to the above process was coated on an aluminum foil using a doctor blade to manufacture a thin electrode plate, and then dried at 135° C. for 3 hours or longer, followed by roll pressing and vacuum drying, thereby completing the manufacture of the positive electrode.

[0138] A 2032-type coin cell battery was manufactured using the positive electrode and Li metal as a counter electrode. A separator (thickness: about 16 µm) formed of a porous polyethylene (PE) film was disposed between the positive electrode and the Li metal counter electrode, and an electrolyte solution was injected therebetween, thereby completing the manufacture of a 2032-type coin cell battery. As the electrolyte solution, a solution prepared by dissolving 1.1 M LiPF6 in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:5 was used.

[0139] Manufacturing Example 2: Manufacturing of coin cell battery

[0140] A coin-cell battery was manufactured in the same manner as in Manufacturing Example 1, except that the nickel-based active material prepared according to Example 2 was used instead of the nickel-based active material of Example 1.

[0141] Comparative Manufacturing Example 1: Manufacturing of coin cell battery

[0142] A coin-cell battery was manufactured in the same manner as in Manufacturing Example 1, except that the nickel-based active material prepared according to Comparative Example 1 was used instead of the nickel-based active material of Example 1.

[0143] Evaluation Example 1: Scanning Electron Microscopy

[0144] Scanning electron microscopy (SEM) was performed on the nickel-based active material precursors of Preparation Examples 1 and 2 and Preparation Comparative Example 1. The scanning electron microscope used here was Magellan 400 L (manufactured by FEI Company), and the cross section of each sample was pre-treated by grinding at 6 kV and 150 μA for 4 hours using CP2 available from JEOL. SEM was performed under the condition of 350 V.

[0145] According to the SEM results, Figure 5 and 6 As shown in, in the nickel-based active material precursors of Preparation Examples 1 and 2, the secondary particles have a multi-center structure including 3 or 4 radial centers. It is also confirmed that each nickel-based active material precursor is composed of secondary particles in which the radial centers respectively included in a plurality of granular structures are isotropically arranged, wherein each granular structure includes a porous core portion and a shell portion, and the shell portion includes primary particles radially arranged on the porous core portion. In contrast, in the nickel-based active material precursor of Preparation Comparative Example 1, a single secondary particle has only one center.

[0146] The nickel-based active material precursors of Preparation Examples 1 and 2 and Comparative Preparation Example 1 were each partially crushed and their cross sections were subjected to SEM. As a result of the analysis, it was confirmed that in the nickel-based active material precursors of Preparation Examples 1 and 2, the primary particles included plate-like particles.

[0147] Evaluation Example 2: Composition Analysis

[0148] The composition of each of the nickel-based active material precursors of Preparation Examples 1 and 2 and Comparative Preparation Example 1 was analyzed by inductively coupled plasma (ICP) analysis, and the results thereof are shown in Table 1 below.

[0149] [Table 1]

[0150]

[0151] As shown in Table 1, it was confirmed that the nickel-based active material precursors of Preparation Example 1 and Preparation Comparative Example 1 had Ni 0.6 Co 0.2 Mn 0.2 (OH)2, and the nickel-based active material precursor of Preparation Example 2 has Ni 0.7 Co 0.15 Mn 0.15 The composition of (OH)2.

[0152] Evaluation Example 3: Initial Charge / Discharge Efficiency (ICE)

[0153] The coin cells manufactured according to Manufacturing Examples 1 and 2 and Manufacturing Comparative Example 1 were each charged and discharged once at 0.1 C and 25° C. to perform a formation operation. Subsequently, each coin cell was subjected to a charge and discharge cycle at 0.1 C to confirm the initial charge / discharge characteristics of each coin cell. The charging process was set so that it started in a constant current (CC) mode and changed to a constant voltage (CV) mode, and then the charging process was cut off at 4.3 V and 0.05 C, and the discharge process was set to be cut off at 3.0 V in CC mode. The initial charge / discharge efficiency (ICE) of each coin cell was measured by the following equation 1, and the results are shown in the following Table 2.

[0154] [Equation 1]

[0155] Initial charge / discharge efficiency [%] = [discharge capacity at the first cycle / charge capacity at the first cycle] x 100

[0156] [Table 2]

[0157]

[0158] As shown in Table 2, the coin-cell batteries of Manufacturing Examples 1 and 2 exhibited improved charge / discharge efficiency at 0.1C (initial characteristics) compared to the case of Manufacturing Comparative Example 1.

[0159] Evaluation Example 4: Charge / Discharge Characteristics (Rate Performance)

[0160] The coin cells of Manufacturing Examples 1 and 2 and Manufacturing Comparative Example 1 were each charged at a constant current of 0.2 C and a constant voltage of 4.3 V, the charging process was cut off at 0.05 C, and then left to stand for 10 minutes, and then each coin cell was discharged under constant current conditions until the voltage reached 3.0 V by changing the current amount to 0.1C, 0.1C, 0.1C, 0.2C, 0.33C, 0.5C, 1C, 2C, and 3C for the 1st to 9th cycles, respectively. That is, for each charge and discharge cycle, the discharge rate was increased to 0.1C, 0.1C, 0.1C, 0.2C, 0.33C, 0.5C, 1C, 2C, and 3C to evaluate the rate performance of each coin cell. The rate performance of each coin cell was measured by the following equation 2, and the results are shown in the following Table 3.

[0161] [Equation 2]

[0162] Rate performance [%] = (discharge capacity when the unit cell is discharged at a certain constant current rate) / (discharge capacity when the unit cell is discharged at a 0.1 C rate (3rd cycle)) x 100

[0163] [Table 3]

[0164]

[0165] As shown in Table 3, the coin-cell batteries of Manufacturing Examples 1 and 2 exhibited similar rate performance and superior specific capacity compared to the coin-cell battery of Manufacturing Comparative Example 1.

[0166] Evaluation Example 5: High Temperature Life Characteristics

[0167] The high temperature life characteristics of the coin cells of Manufacturing Examples 1 and 2 and Manufacturing Comparative Example 1 were evaluated as follows. First, each coin cell was subjected to a charge / discharge process at 0.1 C once to perform a formation operation. Subsequently, each coin cell was subjected to a charge and discharge cycle at 0.1 C to confirm the initial charge / discharge characteristics of each coin cell, and 50 charge and discharge cycles were repeated at 45 ° C and 1 C to measure the cycle characteristics of each coin cell. The charging process was set so that it started in constant current (CC) mode and changed to constant voltage (CV) mode, and then the charging process was cut off at 4.3 V and 0.05 C, and the discharge process was set to be cut off at 3.0 V in CC mode. The measurement results are shown in Table 4 below.

[0168] [Table 4]

[0169]

[0170] As shown in Table 4, the coin-cell batteries of Manufacturing Examples 1 and 2 exhibited excellent high-temperature life characteristics compared with the case of Manufacturing Comparative Example 1.

[0171] As is clear from the foregoing description, when using a nickel-based active material precursor for a lithium secondary battery according to an embodiment, lithium diffusion at the interface between the positive electrode active material and the electrolyte solution can be promoted, and a nickel-based active material into which lithium is more easily diffused can be obtained. In addition, a nickel-based active material in which the insertion and extraction of lithium is promoted and the diffusion distance of lithium ions is shortened can be obtained. The lithium secondary battery manufactured using such a positive electrode active material exhibits improved lithium availability, and exhibits improved capacity and life due to the suppression of the occurrence of cracks in the active material according to charging and discharging.

[0172] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects within each embodiment should typically be considered as available for other similar features or aspects in other embodiments.

[0173] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.

Claims

1. A nickel-based active material precursor for a lithium secondary battery, the nickel-based active material precursor comprising secondary particles each including a plurality of granular structures, wherein each granular structure includes a porous core portion and a shell portion, the core portion includes irregular polyhedral pores, and the shell portion includes primary particles radially arranged on the porous core portion and in multiple layers, wherein the major axis of the primary particles in 60% - 90% of the primary particles constituting the surface of the secondary particles is disposed in the normal direction of the (100) plane or the (110) plane of the primary particles at the outer surface of the secondary particles, the secondary particles have a plurality of radial centers, and the most common particles of the secondary particles have a sphericity of 0.880 to less than 0.950, wherein the nickel-based active material precursor is a compound represented by the following formula 1: [Formula 1] No 1-x-y-z What x Mn y M z (OH)2 in, In formula 1, M is an element selected from the following: boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zirconium (Zr), tungsten (W), and aluminum (Al), and x ≤ (1 - x - y - z), y ≤ (1 - x - y - z), 0 < x < 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < 1 - x - y - z < 1.

2. The nickel-based active material precursor according to claim 1, wherein the secondary particles have multiple centers and are composed of granular structures arranged isotropically.

3. The nickel-based active material precursor according to claim 1, wherein the major axis of the primary particles constituting the surface of the secondary particles points to the normal of the surface of the secondary particles.

4. The nickel-based active material precursor according to claim 1, wherein the primary particles include plate-like particles, wherein the major axis of the plate-like particles is radially arranged, and the ratio of the thickness to the length of the plate-like particles is in the range of 1:2 to 1:

20.

5. The nickel-based active material precursor according to claim 1, wherein the secondary particles have a size of 5 µm to 25 µm.

6. The nickel-based active material precursor according to claim 1, wherein the content of nickel in the nickel-based active material precursor is in the range of 33 mol% to 95 mol% relative to the total content of transition metals, wherein the content of nickel is the same as or greater than the content of manganese, and the content of nickel is the same as or greater than the content of cobalt.

7. The nickel-based active material precursor according to claim 1, wherein the nickel-based active material precursor is selected from: Ni 0.6 Co 0.2 Mn 0.2 (OH)2、Ni 0.7 Co 0.15 Mn 0.15 (OH)2、Ni 0.7 Co 0.1 Mn 0.2 (OH)2、Ni 0.5 Co 0.2 Mn 0.3 (OH)2、Ni 1 / 3Co 1 / 3 Mn 1 / 3 (OH)2、Ni 0.8 Co 0.1 Mn 0.1 (OH)2, and Ni 0.85 Co 0.1 Al 0.05 (OH)2.

8. A method for preparing the nickel-based active material precursor for a lithium secondary battery according to any one of claims 1 - 7, the method comprising: a first operation of supplying feedstock at a first feed rate and stirring the feedstock to form precursor seeds; a second operation of supplying feedstock at a second feed rate to the precursor seeds formed by the first operation and stirring the resulting mixture to grow the precursor seeds by agglomeration of the mixture; and a third operation of supplying feedstock at a third feed rate to the precursor particles grown by the second operation and stirring the resulting mixture to control the growth of the precursor particles. wherein the supply raw materials include a complexing agent, a pH adjusting agent, and a metal raw material for forming a nickel-based active material precursor, For the metal raw material for forming the nickel-based active material precursor, the second feed rate is higher than the first feed rate, and the third feed rate is higher than the second feed rate, and As the first operation, the second operation and the third operation proceed, the stirring power of the reaction mixture is sequentially reduced, wherein the concentration of the complexing agent in the second operation is higher than that in the first operation, wherein the concentration of the complexing agent in the third operation is the same as that in the second operation or higher than that in the first operation.

9. The method of claim 8, wherein: In the metal raw material for forming a nickel-based active material precursor, the second feed rate is increased by 10% to 50% relative to the first feed rate, and the third feed rate is increased by 10% to 50% relative to the second feed rate.

10. The method of claim 8, wherein the metal raw material for forming the nickel-based active material precursor comprises at least one selected from nickel sulfate, nickel nitrate, nickel chloride and nickel fluoride, and optionally comprises at least one selected from manganese sulfate, manganese nitrate, manganese chloride, manganese fluoride, cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt fluoride.

11. The method according to claim 8, wherein the stirring power in the first operation is 1.5 kW / m 3 Up to 4 kW / m 3 In the range of 1 kW / m 3 Up to 3 kW / m 3 In the range of , and the stirring power in the third operation is 0.5 kW / m 3 Up to 2 kW / m 3 within the range.

12. The method of claim 8, wherein: As the first operation, the second operation, and the third operation are performed, the pH of the reaction mixture is reduced or maintained.

13. A nickel-based active material for a lithium secondary battery, the nickel-based active material being obtained from the nickel-based active material precursor according to any one of claims 1 to 7.

14. Lithium secondary batteries, including: A positive electrode comprising the nickel-based active material as claimed in claim 13; a negative electrode; and an electrolyte between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Adjusting industrial vehicle performance

    KR1020180073588A